UJI KETAHANAN BEBERAPA KLON KAKAO (Theobromae cacao L.) TERHADAP PENYAKIT BUSUK BUAH (Phytophthorah palmivora butl) - Aminullah, Moh. Fajri S.; Panggeso, Johanis; Rosmini, Rosmini (AGROTEKBIS, 2017)
Cacao is one of the prioritized commodities of crop plantations in Central Sulawesi. However, the main obstacle faced in the cultivation of cocoa plants is plant pest organisms (OPT). One of the most frequently OPT encountered is black pod rot caused by Phytophtorah palmivora fungus. Based on the above description, this study aimed to determine the resilience of some cacao clones on the development of P. palmivora. Cocoa fruit samples of six different clones were taken from people plantations in Uenuni village, Palolo sub district of Sigi Regency, and brought to the Laboratory of Phytopathology Plant where their resistance to black pod rot disease was tested using a Detached Pod method. The six clones used included Local II (Criolo), M01, Lokal III (Mulia), CRD 60, Local I (Forestero), and Local IV (Hibrida). This study used a Completely Randomized design (CRD) with P. palmivora as a factor. The fungus was inoculated to the fruits of the six cacao clones. An experimental unit consisted of three pieces of cocoa for each clone tested and replicatedthree times.Â  Observations were made on the area size of spots on the fruitâssurface and itsincreasingsizeper day for seven days. After seven days, the largest spot area of 350.79 cm2 was found in the Lokal III (Mulia) clone with the fastest rate of increasing spot size of 58.11 cm2 per day in average and with 0.63 cm thickness of the outer skin and with 0.43 cm thickness of the inner skin suggesting that this clone is very prone to P. palmivora attack. The lowest spot area found in the CRD 60 clone was 12.86cm2 with the rate of increasing spot size 1.91 cm2per day in average, and with 1.03 cm thickness of the outer skin and with 0.77 cm thickness of the inner skin suggesting that this clone belong to a group resistant to P. palmivora attack.Â Keywords: Cacao clone and Fungi P. Palmivora.